2001
DOI: 10.1029/2000ja000394
|View full text |Cite
|
Sign up to set email alerts
|

A statistical study of transient event motion at geosynchronous orbit

Abstract: Abstract. The geosynchronous GOES 5 and GOES 6 satellites frequently observe transient events marked by magnetic field strength increases and bipolar magnetic field signatures lasting several minutes. In this study we report a survey of 87 events observed simultaneously by both GOES spacecraft (for a total of 174 individual observations) from August to December 1984. Events detected in the prenoon sector outnumbered those in the postnoon sector by about a 3 to 1 ratio. The distribution of the events versus loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…This then casts some doubt as to the correct interpretation of such signatures. In addition, some statistical studies [e.g., Sanny et al, 1996Sanny et al, , 2001 of FTE-type signatures showed no southward IMF dependence, and thus provide support for the pressure-pulse interpretation. However, detailed studies of particle distributions during ''crater'' FTE observations [e.g., Smith and Owen, 1992] indicate that not all the signatures can be accommodated in the Sibeck [1990Sibeck [ , 1992 picture, and it seems thus appropriate to retain the reconnection model of the formation for at least some events.…”
Section: Introductionmentioning
confidence: 80%
“…This then casts some doubt as to the correct interpretation of such signatures. In addition, some statistical studies [e.g., Sanny et al, 1996Sanny et al, , 2001 of FTE-type signatures showed no southward IMF dependence, and thus provide support for the pressure-pulse interpretation. However, detailed studies of particle distributions during ''crater'' FTE observations [e.g., Smith and Owen, 1992] indicate that not all the signatures can be accommodated in the Sibeck [1990Sibeck [ , 1992 picture, and it seems thus appropriate to retain the reconnection model of the formation for at least some events.…”
Section: Introductionmentioning
confidence: 80%
“…The authors used the typical properties of these layers to predict the signatures and showed that this scenario could explain the features of the crater-type FTEs. Moreover, some statistical studies (e.g., Kawano et al, 1992;Sanny et al, 1996Sanny et al, , 2001) of FTE-type signatures showed no significant southward IMF dependence, thus, they provide support for the pressure-pulse interpretation. Sibeck et al (2005) considered the properties of FTEs observed by Interball-1 on a statistical basis and they found that events observed on the mid-latitude magnetopause, equatorward of the cusps, exhibit a strong tendency to occur for Published by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 87%
“…The results of this study should be compared with those obtained by Sanny et al (2001), who surveyed the occurrence patterns and motion of a particular category of event at geosynchronous orbit, namely flux transfer events. Each of these events was identified on the basis of bipolar signatures in the direction normal to the nominal magnetopause and impulsive increases in the magnetic field strength.…”
Section: Discussionmentioning
confidence: 99%